2021
DOI: 10.3389/fcvm.2021.706852
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil-to-Lymphocyte Ratio Is an Important Indicator Predicting In-Hospital Death in AMI Patients

Abstract: Objective: To explore the role of neutrophil-to-lymphocyte ratio (NLR) in predicting the short-term prognosis of NSTEMI and STEMI.Methods: This study was a single-center, retrospective and observational study. 2618 patients including 1289 NSTMI and 1329 STEMI patients were enrolled from June 2013 to February 2018 in Zhongda Hospital, Southeast University. The demographic information, clinical characteristics, medical history, laboratory examination, treatment, and outcome of individuals at admission and during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 28 publications
1
35
0
3
Order By: Relevance
“…In COVID-19 patients, neutrophilia associated with lymphopenia was observed in patients with increased disease severity and with poor prognosis ( Picchi et al, 2021 , Yang et al, 2020 , Zhu et al, 2021 ). A number of studies showed a correlation between markers derived from standard blood count tests, such as neutrophil-to-lymphocyte ratio (NLR), derived NLR ratio (dNLR, neutrophil count divided by the result of WBC count minus neutrophil count), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) and systematic inflammatory response in a number of age-related diseases, including cancer ( Xu et al, 2021 , Ying et al, 2014 ), type 2 diabetes mellitus (T2DM) ( Tong et al, 2004 ), cardiovascular diseases (CVD) ( Bhat et al, 2013 , Ji et al, 2021 ), and stroke ( Cai et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 patients, neutrophilia associated with lymphopenia was observed in patients with increased disease severity and with poor prognosis ( Picchi et al, 2021 , Yang et al, 2020 , Zhu et al, 2021 ). A number of studies showed a correlation between markers derived from standard blood count tests, such as neutrophil-to-lymphocyte ratio (NLR), derived NLR ratio (dNLR, neutrophil count divided by the result of WBC count minus neutrophil count), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) and systematic inflammatory response in a number of age-related diseases, including cancer ( Xu et al, 2021 , Ying et al, 2014 ), type 2 diabetes mellitus (T2DM) ( Tong et al, 2004 ), cardiovascular diseases (CVD) ( Bhat et al, 2013 , Ji et al, 2021 ), and stroke ( Cai et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…After the adjustment of the variable, the above conclusion still holds. Unlike the previous study on this topic ( 21 24 ), our research further clarified the exact relationship between NLR and two types of mortality, and we also identified the valuable threshold points. Besides, we constructed a prognostic-related nomogram model for the first time.…”
Section: Discussionmentioning
confidence: 63%
“…After that, neutrophils will release cytokines, which also affect the activation of lymphocytes, and participate in inflammation. Inflammatory cytokines released by neutrophils accelerate the progression of CVDs ( 24 ). Therefore, many CVDs, such as coronary atherosclerotic heart disease and acute myocardial infarction, are considered to be the result of inflammation ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation might be additional possible explanation for the association between increased LDH level and adverse prognosis in patients after cardiac surgery. Accumulating evidence revealed that inflammatory biomarkers, such as NLR [ 34 , 35 ] and CRP [ 36 ], have been reported to be correlated with adverse outcomes of CHD or acute myocardial infarction. There is a paucity of reports about the prognostic effect of inflammatory markers in valve disease.…”
Section: Discussionmentioning
confidence: 99%